2020
DOI: 10.3390/electronics9020251
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-Wave Communications

Abstract: For the last few decades, the millimeter wave (mmWave) frequency band (30–300 GHz) has been seen as a serious candidate to host very high data rate communications [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Microwave communication came into application in the 1950s as an advanced communication technology, and uses electromagnetic waves with a frequency between 300 MHz and 300 GHz and a wavelength between 1 mm and 1 m for communication, which is divided into three frequency bands: ultra high frequency (UHF), 300 MHz to 3 GHz, super high frequency (SHF), 3–30 GHz, and extremely high frequency (EHF), 30–300 GHz 1,2 . Future mobile communication will be developed towards millimeter‐wave frequency range concentrated in 24.25–52.6 GHz 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave communication came into application in the 1950s as an advanced communication technology, and uses electromagnetic waves with a frequency between 300 MHz and 300 GHz and a wavelength between 1 mm and 1 m for communication, which is divided into three frequency bands: ultra high frequency (UHF), 300 MHz to 3 GHz, super high frequency (SHF), 3–30 GHz, and extremely high frequency (EHF), 30–300 GHz 1,2 . Future mobile communication will be developed towards millimeter‐wave frequency range concentrated in 24.25–52.6 GHz 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, HfO 2 has attracted extensive scientific interest as a promising oxide material, especially for the unique ferroelectricity in HfO 2 ‐based films 6 . Ferroelectricity in Si, Y, and Al doped HfO 2 films, 6–10 even undoped HfO 2 films, 11 has been reported on. However, there is little research on HfO 2 ceramics, and no ferroelectricity has been reported in HfO 2 ‐based ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Different applications, such as complementing terrestrial RANs with unmanned arial vehicles (UAVs), can be cost-effective and flexible strategies with the 5G radio access networks, as reported in [2]. Furthermore, the mm-wave technology is capable of meeting the increasing demands of wireless applications [3][4][5][6]. However, in the electrical domain, the generation of mm waves with high frequency remains a challenge due to the current restrictions on frequency responses of electronic devices and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…More than ten times more than nowadays will be the increment of the number of connected devices. The transition from microwave to millimeter-wave (MMW) frequency bands may be achieved in gradual steps to take advantage of the higher capacity, decreasing the system latency, higher bandwidth, as well as a large amount of available spectrum [1][2][3][4]. There are many frequency bands assigned by the FCC [3,5].…”
Section: Introductionmentioning
confidence: 99%